Knock-Out of DHTKD1 Alters Mitochondrial Respiration and Function, and May Represent a Novel Pathway in Cardiometabolic Disease Risk - Wang, Chuan; Calcutt, M. Wade; Ferguson, Jane F. (Frontiers in Endocrinology, 2021)
Cardiometabolic disease affects the majority of individuals worldwide. The metabolite α-aminoadipic acid (2-AAA) was identified as a biomarker of Type 2 Diabetes (T2D). However, the mechanisms underlying this association remain unknown. DHTKD1, a central gene in the 2-AAA pathway, has been linked to 2-AAA levels and metabolic phenotypes. However, relatively little is known about its function. Here we report that DHTKD1 knock-out (KO) in HAP-1 cells leads to impaired mitochondrial structure and function. Despite impaired mitochondrial respiration and less ATP production, normal cell proliferation rate is maintained, potentially through a series of compensatory mechanisms, including increased mitochondrial content and Akt activation, p38, and ERK signaling. Common variants in DHTKD1 associate with Type 2 Diabetes and cardiometabolic traits in large genome-wide association studies. These findings highlight the vital role of DHTKD1 in cellular metabolism and establish DHTKD1-mediated mitochondrial dysfunction as a potential novel pathway in cardiometabolic disease.